Sustainable Practices in Food Service Management: Exploring Eco-Friendly Restaurants in Indonesia Tourism Cities - Anisa Zahwa Akbara; Andy Mulyana; Hubertina Karolina Ngarbingan (Jurnal Riset Ekonomi Manajemen (REKOMEN), 2025)
Sustainable practices in the food service industry are gaining prominence in tourism-driven Indonesian cities like Jakarta, Bandung, and Labuan Bajo (East Nusa Tenggara), where restaurants significantly impact the environment. Therefore, this study examines sustainable practices in food service management by exploring eco-friendly restaurants in Indonesia's tourism cities through a quantitative research approach. An online questionnaire was distributed, collecting responses from 257 participants to assess the impact of Sustainable Sourcing Ingredients, Waste Management Practices, and Energy Efficiency Measures on Customer Perception, with Customer Experience acting as a moderate variable. The results show that sustainable sourcing, waste management, and energy efficiency significantly influence customer perception of eco-friendly restaurants. Customer experience further strengthens these relationships. The study emphasizes the need for better communication and transparency, suggesting tools like eco-labeling, storytelling, and digital engagement. It offers valuable insights from a developing tourism context to support sustainable food service management and promote responsible consumer behavior.